ATP13A2 and alpha-synuclein: a metal taste in autophagy - da Fonseca, Tomás Lopes (2014)
© The Korean Society for Brain and Neural Sciences. This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.